Real Business Cycles with Capital Maintenance - Alice Albonico; Sarantis Kalyvitis; Evi Pappa (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
We develop a stochastic general equilibrium model in which maintenance endogenously affects the capital depreciation rate. The model performs well in generating maintenance series that match closely existing survey-based measures for Canada. Maintenance is procyclical and comoves almost always with output. Investmentspecific shocks are the only disturbances that induce a negative correlation between output and maintenance. This feature is crucial for the identification of such shocks in the short run. We use Bayesian estimation to obtain the time profile of equipment capital depreciation in Canadian manufacturing. The depreciation rate has been quite volatile and procyclical over the last 50 years.
Keywords: E22; E32; E37; 330; real business cycle; technology shocks; endogenous capital depreciation; maintenance